Do Independent Commissioners Control the Effect of Family-Owned Business Characteristics on Dividend Policy? A Study in Indonesian Manufacturing Companies - Ernie HENDRAWATY; Sri HASNAWATI; Lia PURNAMASARI (International Journal of Environmental, Sustainability, and Social Science, 2021)
This study aims to determine the role of independent Commissioners to control the effect of family-owned business characteristics on dividend policy. This study construct panel data that estimate using panel regression with a fixed-effect model. The model is estimated using financial data of 64 Indonesian manufacturing companies that were observed from the period 2016-2018. The result showed that family-owned business characteristics have a positive effect on dividens. The Independent Commisioners were able to control the effect of family business characteristics on the dividend policy. The Independent Commissioners have a role in reducing the positive effect of family-owned businesses characteristics on dividends.